Building Students’ Social Awareness through Multicultural Education - Sri Ilham Nasution; Ahmad Fauzan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Social awareness is a vital character trait shaped by educational patterns and internalized values. One of the most effective ways to cultivate this trait is through multicultural education, particularly when implemented in school settings. This educational approach fosters key attitudes among students—such as respect, acceptance of differences, and the ability to collaborate across ethnic and cultural boundaries. Through these attitudes, students develop a deeper national consciousness grounded in an appreciation for diversity. This study aims to explore effective pedagogical strategies for internalizing cultural diversity values and to identify the challenges educators face in this process. The goal is to move beyond merely recognizing differences as social realities and toward embracing them as strengths that support a harmonious and inclusive society. The outcome of this research is the development of a contextual multicultural education model tailored for school environments. This model seeks to equip students not only with knowledge about cultural diversity but also with the social competencies to act inclusively, fairly, and tolerantly. Multicultural education, therefore, serves as a foundational element in shaping a generation that is aware of human dignity and capable of coexisting peacefully within a pluralistic society. The study adopts a descriptive qualitative method, relying on conceptual analysis of previous research, relevant theories, and credible academic sources to gain a comprehensive understanding of how multicultural education can effectively nurture students’ social awareness.